Aesthetic Emotions Across Arts: A Comparison Between Painting and Music - Miu, Andrei C.; Pițur, Simina; Szentágotai-Tătar, Aurora (Frontiers in Psychology, 2016)
Emotional responses to art have long been subject of debate, but only recently have they started to be investigated in affective science. The aim of this study was to compare perceptions regarding frequency of aesthetic emotions, contributing factors and motivation which characterize the experiences of looking at painting and listening to music. Parallel surveys were filled in online by participants (N = 971) interested in music and painting. By comparing self-reported characteristics of these experiences, this study found that compared to listening to music, looking at painting was associated with increased frequency of wonder and decreased frequencies of joyful activation and power. In addition to increased vitality, as reflected by the latter two emotions, listening to music was also more frequently associated with emotions such as tenderness, nostalgia, peacefulness and sadness. Compared to painting-related emotions, music-related emotions were perceived as more similar to emotions in other everyday life situations. Participants reported that stimulus features and previous knowledge made more important contributions to emotional responses to painting, whereas prior mood, physical context and the presence of other people were considered more important in relation to emotional responses to music. Self-education motivation was more frequently associated with looking at painting, whereas mood repair and keeping company motivations were reported more frequently in relation to listening to music. Participants with visual arts education reported increased vitality-related emotions in their experience of looking at painting. In contrast, no relation was found between music education and emotional responses to music. These findings offer a more general perspective on aesthetic emotions and encourage integrative research linking different types of aesthetic experience.